Glass Transition Temperature and Microhardness of Compatible and Incompatible Elastomer/Plastomer Blends (Journal of Bangladesh Academy of Sciences, 2009)
Glass transition temperature (Tg) of core-shell particles-toughened poly(methyl- methacrylate) (CSPTPMMA) and natural rubber-toughened PMMA (NRTPMMA), which are basically the PMMA/elastomer blends with different concentrations of elastomer heterogeneously distributed in the samples, was investigated by means of differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA) and microindentation technique (MT). Microhardness (H) of the samples was measured using MT. Core-shell particles (CSP) with a rubbery shell and natural rubber (NR) were used as reinforcing materials for the production of compatible and incompatible blends, respectively. Results reveal a good correlation of the glass transition temperature (Tg) obtained from DSC and DMA, and that deduced from MT.  The H-value of each sample is compared with its Tg-value. Increase of Tg with the increase of H, which is a general behavior of polymers, is not maintained in the both blends investigated. Contrary to expectation, H is shown to decrease with increasing glass transition temperature in case of CSP-toughened compatible blends while it decreases with the decrease of Tg-value only in case of NR-modified incompatible blends for lower NR concentration (